Becoming Resilient: Promoting the Mental Health and Well-Being of Immigrant Women in a Canadian Context - Judith A. MacDonnell; Mahdieh Dastjerdi; Nimo Bokore; Nazilla Khanlou (Nursing Research and Practice)
This paper reports on grounded theory findings that are relevant to promoting the mental health and well-being of immigrant women in Canada. The findings illustrate how relationships among settlement factors and dynamics of empowerment had implications for “becoming resilient” as immigrant women and how various health promotion approaches enhanced their well-being. Dimensions of empowerment were embedded in the content and process of the feminist health promotion approach used in this study. Four focus groups were completed in Toronto, Ontario, Canada with 35 racialized immigrant women who represented diverse countries of origin: 25 were from Africa; others were equally represented from South Asia (5), Asia (5), and Central or South America and the Caribbean (5). Participants represented diverse languages, family dynamics, and educational backgrounds. One focus group was conducted in Somali; three were conducted in English. Constructivist grounded theory, theoretical sampling, and a critical feminist approach were chosen to be congruent with health promotion research that fostered women’s empowerment. Findings foreground women’s agency in the study process, the ways that immigrant women name and frame issues relevant to their lives, and the interplay among individual, family, community, and structural dynamics shaping their well-being. Implications for mental health promotion are discussed.